1.5 Tesla MRI-Conditional 12-lead ECG for MR Imaging and Intra-MR Intervention - Tse, Zion Tsz Ho (2014)
PROPOSE: High-fidelity 12-lead Electrocardiogram (ECG) is important for physiological monitoring of patients during MR-guided intervention and cardiac MR imaging. Issues in obtaining non-corrupted ECGs inside MRI include a superimposed Magneto-Hydro-Dynamic (MHD) voltage, gradient-switching induced-voltages, and radiofrequency (RF) heating. These problems increase with magnetic field. We intended to develop and clinically validate a 1.5T MRI-conditional 12-lead ECG system. METHODS: The system was constructed, including transmission-lines to reduce radio-frequency induction, and switching-circuits to remove induced voltages. Adaptive filters, trained by 12-lead measurements outside MRI and in two orientations inside MRI, were used to remove MHD. The system was tested on ten (one exercising) volunteers and four arrhythmia patients. RESULTS: Switching circuits removed most imaging-induced voltages (residual noise <3% of the R-wave). MHD removal provided intra-MRI ECGs that varied by <3.8% from those outside the MRI, preserving the true ST segment. In premature-ventricular-contraction (PVC) patients, clean ECGs separated PVC and sinus-rhythm beats. Measured heating was <1.5 C(0). The system reliably acquired multiphase (SSFP) wall-motion-cine and phase-contrast-cine scans, including in subjects where 4-lead gating failed. The system required a minimum TR of 4ms to allow robust ECG processing. CONCLUSION: High-fidelity intra-MRI 12-lead ECG is possible.